The effect of court surfaces on physiological responses and game activities of recreational senior tennis players - Bulent Kilit; Ersan Arslan; Yusuf Soylu (Pensar en Movimiento)
Previous research has predominantly focused on the effects of different court surfaces on the performance responses of professional and young tennis players. However, studies concerning recreational senior tennis players are limited. Therefore, the purpose of this study was to investigate the effects of hard-court (HC) and clay-court (CC) surfaces on the game activities and physiological responses of recreational senior tennis players. Twenty-two recreational senior tennis players (44.2 ± 3.3 years) played two singles matches each, one on an HC and the other on CC, with heart rate responses and time-motion characteristics (TMC) monitored via portable GPS devices. Video recordings revealed variables including effective playing time (EPT), rally duration (DR), strokes per rally (SPR), and rest time between rallies (RT). The results show significant differences between the court surfaces: on CC, players exhibited a higher-average heart rate (152.8 ± 20.3 beats per min vs. 143.7 ± 18.5 on HC, p<0.001), longer rally durations (12.4 ± 8.5 sec vs. 8.1 ± 7.8 on HC, p<0.001), and increased total distance covered (3027.9 ± 396 m vs. 2647.6 ± 378 on HC, p<0.001). Additionally, HC induced significantly faster rally speeds compared to CC (0.70 ± 0.25 shots/s vs. 0.59 ± 0.17 on CC, p<0.001). These results suggest that CC are associated with higher physiological responses and require more game activity from the players than HC. This study contributes to the understanding of how the court surface impacts middle-aged recreational players, indicating that training and preparation should be adapted to meet the unique demands of different court surfaces.